Effect Of Theoretical And Institutional Factors On The Adoption Of E-Learning - Okantey, Mateko; Addo, Hillar (European Scientific Journal, ESJ, 2016)
This paper examined the effect of theoretical and institutional factors that influenced the adoption of e-learning in Universities in Ghana. The study sought to improve understanding of the motivational factors behind the adoption of e-learning systems. This study extended the original Technology Acceptance Model (TAM) to include institutional factors. A sample of 600 lecturers was drawn from both private and public universities in Ghana. Correlation analysis was used to determine the relationship between e-learning and the theoretical factors as well as the relationship between e-learning adoption and institutional factors. Linear regression analysis was used to determine whether the theoretical factors predict e-learning adoption. The study revealed that e-learning was positively correlated to all the theoretical factors discussed. It was observed that significant relationship existed between Perceived Usefulness (PU) and e-learning, while the weakest relationship existed between e-learning and Perceived Ease of Use (PEOU). The research concluded that a lecturer’s adoption of e-learning depended on PEOU as well as PU. However, a lecturer’s adoption of e-learning was more dependent on a lecturer’s PU, that is, the degree to which the lecturer believed that using a particular system would enhance his or her job performance.